JOMH 2021
DOI: 10.31083/jomh.2021.038
|View full text |Cite
|
Sign up to set email alerts
|

Effects of psoriasis and metabolic syndrome on male sexual functions

Abstract: Background and Objective: Psoriasis is a chronic inflammatory systemic skin disease triggered by psychological, genetic and environmental factors. The effect of psoriasis on sexual health has not been fully elucidated. Coexistence of psychiatric disorders also affects negatively the life quality of psoriasis patients. This study investigates the relationship between the severity of the current illness, psychosocial health problems and coexisting metabolic syndrome on sexual health in male patients with psoriasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Psoriasis seriously affects the daily life of patients, and it is reportedly found to relapse even after treatment in some of the patients. 6,7 It is also reported that keratinocytes are excessively proliferated and abnormally differentiated, and inflammatory cells are infiltrated into the dermis and epidermis. 8 Although aberrant interactions between immune cells and keratinocytes have been identified to exercise an important role in the pathogenesis of psoriasis, 9 the detailed mechanism underlying psoriasis is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Psoriasis seriously affects the daily life of patients, and it is reportedly found to relapse even after treatment in some of the patients. 6,7 It is also reported that keratinocytes are excessively proliferated and abnormally differentiated, and inflammatory cells are infiltrated into the dermis and epidermis. 8 Although aberrant interactions between immune cells and keratinocytes have been identified to exercise an important role in the pathogenesis of psoriasis, 9 the detailed mechanism underlying psoriasis is still unclear.…”
Section: Introductionmentioning
confidence: 99%